Coronavirus detection in the clinical microbiology laboratory: Are we ready for identifying and diagnosing a novel virus? (2020)
ndemic species of coronaviruses (HCoV-OC43, HCoV-229E, HCoV-NL63, and HCoVHKU1) are frequent causes of upper respiratory tract infections. The molecular diagnosis of the four species has become integrated into most of the comprehensive respiratory molecular panels used for routine diagnosis. Three highly pathogenic coronaviruses have been associated with outbreaks and epidemics and have challenged clinical microbiology laboratories to quickly develop assays for diagnosis. Their initial characterization was achieved by molecular methods that included pan-coronavirus PCR, amplicon sequencing, and whole genome sequencing. Molecular diagnostic methods were developed and made available mainly at public health laboratories or the CDC. With the great advance in metagenomic whole genome sequencing directly from clinical specimens, diagnosis of novel coronaviruses could be quickly implemented into the workflow of managing cases of pneumonia of unknown etiology, which will markedly impact the time of the initial characterization and accelerate the initiation of outbreak control measures.